Expanding Ecotheology to Embrace the Earth-Moon System. Issue 2 (3rd April 2022) - Rappaport, Margaret Boone; Corbally, Christopher; Campa, Riccardo
ABSTRACT: An enlarged purview for amplification of religious doctrine can become necessary for a spacefaring species. Settlement of distant planetary bodies involves both technological and theological issues. The authors apply this notion to environmental preservation of the Earth, Earth's Moon, and cislunar space between Earth and Moon, as a unit. In expanding environmental protection beyond Earth to the new cislunar unit, humans take an important step in settling the Moon responsibly. The relationships of immanence and transcendence to the new environmental unit provide examples of the conceptual tasks ahead. Profiles in Ecotheology round out the analysis and point toward future roles.